Application of the Topological Optimization Method of a Connecting Rod Forming by the BESO Technique in ANSYS APDL - Myagkov, L. (Springer, 2020)
The article presents the result of optimizing the shape of a diesel engine connecting rod with the help of the developed method. The objective function, constraints and performance criteria necessary to perform the optimization are determined. After optimization, the analysis of the obtained results was performed. At the end of the work it was concluded that it is necessary to perform a detailed elastohydrodynamic calculation of sliding bearings. Such a calculation would allow the introduction of a more adequate criterion for the connecting rod performance criterion. The article also identifies further ways of developing the method. Â© 2020, Springer Nature Switzerland AG.